2018
DOI: 10.1177/0361198118794066
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Value of Land and Landside Access to Fund Port Infrastructure in Texas

Abstract: This paper introduces port authority transportation reinvestment zones (TRZs), a funding tool created by the Texas Legislature to help fund long-term economic development port projects. TRZs were first introduced in Texas in 2007 as a tool to allow county and municipal governments to raise funds to help pay for transportation improvements using the property tax mechanism. Since then, the legislation has been amended to include other transportation modes, such as transit, rail, and parking facilities. Amendment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The extent of available funds drives most large-scale infrastructure projects undertaken by a public authority. Several studies have shown that improvement of rail-related infrastructure (such as station development) has resulted in increases in real estate value and businesses prosper around the improvements (Cao and Porter-Nelson, 2016;Aldrete et al, 2018). However, techniques to exploit all aspects of economic benefits still need to be evaluated and adopted in practice.…”
Section: Other Funding Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of available funds drives most large-scale infrastructure projects undertaken by a public authority. Several studies have shown that improvement of rail-related infrastructure (such as station development) has resulted in increases in real estate value and businesses prosper around the improvements (Cao and Porter-Nelson, 2016;Aldrete et al, 2018). However, techniques to exploit all aspects of economic benefits still need to be evaluated and adopted in practice.…”
Section: Other Funding Mechanismsmentioning
confidence: 99%
“…Determining value capture generated could be extremely useful in funding such at-grade separation projects. Applications of such value capture techniques have proven to be very promising for other similar large-scale transportation projects elsewhere in the nation (Aldrete et al, 2018).…”
Section: Data Collectionmentioning
confidence: 99%
“…Bottasso et al (2018) found that the infrastructure construction of ports in Brazil was closely related to the robust growth of export trade of Brazil. Aldrete et al (2018) suggested to concentrate foundations on port infrastructure construction in Texas. took Shanghai port as an example to study the relative growth of port throughput and urban population, and put forward that throughput was a key contributor to port development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…State Bill 1747 was passed in 2013 (section 8) to create a state Transportation Infrastructure Fund (TIF) with funds from various sources to manage a grant program for the County Energy Transportation Reinvestment Zone (CERTZ). It aims at planning, constructing, reconstructing, and maintaining of infrastructure to prevent the deterioration of roads, bridges, culverts, and other infrastructure caused by exploration, development or production of oil and gas (Aldrete et al, 2016; Stark, 2013).…”
Section: Introductionmentioning
confidence: 99%